Complementing the European earth observation and geographic information body of knowledge with a business‐oriented perspective. Issue 3 (14th May 2020) - Hofer, Barbara; Casteleyn, Sven; Aguilar‐Moreno, Estefanía; Missoni‐Steinbacher, Eva‐Maria; Albrecht, Florian; Lemmens, Rob; Lang, Stefan; Albrecht, Jochen; Stelmaszczuk‐Górska, Martyna; Vancauwenberghe, Glenn; Monfort‐Muriach, Aida
Abstract: A body of knowledge (BoK) is an inventory of knowledge or concepts of a domain that serves as a reference vocabulary for various purposes, such as the development of curricula, the preparation of job descriptions, and the description of occupational profiles. To fulfill its purpose, a BoK needs to be up‐to‐date and ideally widely accepted by academia as well as the private and public sectors. This article presents the initiative taken in the Earth observation and geographic information (EO*GI) domain to provide a current, comprehensive education‐ and business‐oriented EO*GI BoK called EO4GEO BoK. In particular, an approach to strengthen the business‐oriented perspective in the EO4GEO BoK is presented. This approach is based on the analysis of professional tasks and the mapping of these tasks to concepts and skills contained in the BoK. A critical reflection of the proposed approach that is based on the experiences gained during a workshop complements this article.